Genetic Analysis through OtoSeq of Pakistani Families Segregating Prelingual Hearing Loss. Issue 3 (14th June 2013) - Shahzad, Mohsin; Sivakumaran, Theru A.; Qaiser, Tanveer A.; Schultz, Julie M.; Hussain, Zawar; Flanagan, Megan; Bhinder, Munir A.; Kissell, Diane; Greinwald, John H.; Khan, Shaheen N.; Friedman, Thomas B.; Zhang, Kejian; et al.
Abstract : Objective: To identify the genetic cause of prelingual sensorineural hearing loss in Pakistani families using a next‐generation sequencing (NGS)–based mutation screening test named OtoSeq. Study Design: Prospective study. Setting: Research laboratory. Subjects and Methods: We used 3 fluorescently labeled short tandem repeat (STR) markers for each of the known autosomal recessive nonsyndromic (DFNB) and Usher syndrome (USH) locus to perform a linkage analysis of 243 multigenerational Pakistani families segregating prelingual hearing loss. After genotyping, we focused on 34 families with potential linkage to MYO7A, CDH23, and SLC26A4 . We screened affected individuals from a subset of these families using the OtoSeq platform to identify underlying genetic variants. Sanger sequencing was performed to confirm and study the segregation of mutations in other family members. For novel mutations, normal hearing individuals from ethnically matched backgrounds were also tested. Results: Hearing loss was found to co‐segregate with locus‐specific STR markers for MYO7A in 32 families, CDH23 in 1 family, and SLC26A4 in 1 family. Using the OtoSeq platform, a microdroplet PCR‐based enrichment followed by NGS, we identified mutations in 28 of the 34 families including 11 novel mutations. Sanger sequencing of these mutations showed 100% concordance with NGS data and co‐segregation of the mutant alleles with the hearing loss phenotype in the respective families. Conclusion: Using NGS‐based platforms like OtoSeq in families segregating hearing loss will contribute to the identification of common and population‐specific mutations, early diagnosis, genetic counseling, and molecular epidemiology.